EFEKTIVITAS TELUR AYAM REBUS DAN MADU TERHADAP PENINGKATAN KADAR HEMOGLOBIN PADA REMAJA PUTRI DENGAN ANEMIA RINGAN DI PMB S KECAMATAN CIMANGGU KABUPATEN PANDEGLANG BANTEN TAHUN 2025 - Sopa Nurhawa Oktapia; Retno Sugesti (PT. Hasba Edukasi Mandiri, 2025)
Introduction: The 2021 prevalence of anemia among women of childbearing age aged 15-49 years according to the WHO was 29.9% globally (WHO, 2021). Based on the 2018 Basic Health Research (Riskesdas), Indonesia is a developing country in Southeast Asia, with an anemia prevalence of 32% among women aged 15-24 years. The proportion of anemia in women was 27.2% and in men 20.3%, indicating a higher prevalence of anemia in women compared to men (Dwi Santy Damayanti et al. 2022). Based on the Basic Health Research (Riskesdas) (2019), the national incidence of anemia was reported to be 21.7%, with 18.4% occurring in men and 23.9% in women. Objective: To provide midwifery care and determine the effectiveness of boiled chicken eggs and honey on increasing hemoglobin levels in adolescent girls with mild anemia. Method: This is a qualitative research design with a case study approach. The sample used was adolescent girls with mild anemia. They received the intervention for 14 days. Results: The administration of honey and iron tablets resulted in a faster increase in hemoglobin levels compared to the adolescent girls given the intervention of boiled chicken eggs and iron tablets, with a difference of 0.4 g/dl. Conclusions and Recommendations: It is hoped that the community, especially adolescent girls, can implement the use of honey and eggs to prevent anemia.